Electrochemical tuning of olivine-type lithium transition-metal phosphates as efficient water oxidation catalysts1. Issue 6 (3rd June 2015) - Liu, Yayuan; Wang, Haotian; Lin, Dingchang; Liu, Chong; Hsu, Po-Chun; Liu, Wei; Chen, Wei; Cui, Yi
<x xml:space="preserve">Abstract</x> Electrochemical lithium tuning of olivine-type lithium transition metal phosphates results in greatly enhanced oxygen evolution catalytic activity.